Saturday, 16 JUNE 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.3513
|View full text |Cite
|
Sign up to set email alerts
|

SAT0266 Use of conventional synthetic dmards and biological dmards in patients with enteropathic spondyloarthritis: a combined gastro-rheumatological approach

Abstract: BackgroundEnteropathic spondyloarthritis (eSpA) is a chronic autoimmune disease associated with inflammatory bowel disease (IBD) that is poorly diagnosed and managed.ObjectivesTo assess the diagnostic and therapeutic effect of a combined gastro-rheumatological approach in eSpA patients.MethodsIBD-patients with joint pain referred to a dedicated rheumatologist by gastroenterologist were enrolled. Clinical and biochemical variables, SpA and intestinal disease activity measures, and treatment (biologic; bDMARDs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Although rates of peripheral and axial involvement in eSpA are different in the studies, peripheral involvement rate is higher than the rate of axial involvement. In the study by Chimenti et al (12), 65% of eSpA patients had peripheral involvement, while 35% of the patients had axial involvement. In another study, the rate of only peripheral involvement was 53% in eSpA patients, while the rate of only axial involvement was 26% (13).…”
Section: Discussionmentioning
confidence: 91%
“…Although rates of peripheral and axial involvement in eSpA are different in the studies, peripheral involvement rate is higher than the rate of axial involvement. In the study by Chimenti et al (12), 65% of eSpA patients had peripheral involvement, while 35% of the patients had axial involvement. In another study, the rate of only peripheral involvement was 53% in eSpA patients, while the rate of only axial involvement was 26% (13).…”
Section: Discussionmentioning
confidence: 91%
“…In a small case series of 8 patients with refractory CD, authors retrospectively demonstrated a potential clinical effect in selected subgroup of difficult-to-treat CD patients. [2] In particular, 4 patients had a concomitant SpA and golimumab was effective in 2 of them while residual clinical symptoms and paradoxic psoriasis were observed in the other 2 patients. [2] …”
Section: Discussionmentioning
confidence: 95%
“… [2] In particular, 4 patients had a concomitant SpA and golimumab was effective in 2 of them while residual clinical symptoms and paradoxic psoriasis were observed in the other 2 patients. [2] …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations